2020
DOI: 10.1007/s00134-020-06182-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of early prone position for COVID-19 patients with severe hypoxia: a single-center prospective cohort study

Abstract: Full author information is available at the end of the article Xuefeng Zang and Qian Wang contributed equally to this work. Hua Zhou, Sanhong Liu and Xinying Xue contributed equally to this work. The members of the COVID-19 Early Prone Position Study Group are listed in the Acknowledgements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
132
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(144 citation statements)
references
References 4 publications
1
132
0
11
Order By: Relevance
“…Reduction of respiratory rate with APP was demonstrated in ve studies (n = 90) [10,28,36,40,41], but not in two other studies (n = 34) [33,45]. Finally, signi cantly reduced PaCO2 was demonstrated only in a single small study (n = 9) [35], while no changes in PaCO2 were observed in a larger report (n = 46) [14].…”
Section: Resultsmentioning
confidence: 81%
“…Reduction of respiratory rate with APP was demonstrated in ve studies (n = 90) [10,28,36,40,41], but not in two other studies (n = 34) [33,45]. Finally, signi cantly reduced PaCO2 was demonstrated only in a single small study (n = 9) [35], while no changes in PaCO2 were observed in a larger report (n = 46) [14].…”
Section: Resultsmentioning
confidence: 81%
“…Finally, an important limitation not mentioned by the authors is the possibility of methodological bias since the method in which patients were allocated to the groups was not described. Although we recognize the importance of the study by Zang et al [1], we hope that results from ongoing randomized controlled trials (e.g., NCT04383613, NCT04359797, NCT04350723, NCT04347941, NCT04477655 and NCT04344587) demonstrate greater certainty about the effects of the early prone position in non-intubated COVID-19 patients with hypoxia on intubation and mortality rates.…”
Section: Dear Editormentioning
confidence: 90%
“…We have read with interest the study by Zang et al [1] recently published in Intensive Care Medicine, which showed greater 90-day survival in the group of nonintubated COVID-19 patients with severe hypoxia who performed early prone position (56.5%) compared to the group who did not (24.3%). This result is an important differential in relation to the several studies previously published.…”
Section: Dear Editormentioning
confidence: 96%
See 2 more Smart Citations